Changing the landscape of mental health among college students: a community case study of a course on learning sustainable well-being - Dobkins, Karen; Dickenson, Janna; Lindsay, Debra; Bondi, Taylor (Frontiers in Public Health, 2023)
Our society is facing an unprecedented mental health crisis, with nearly one in two people being affected by mental health issues over their lifespan. This trend is especially noticeable among college students, who undergo significant shifts in social, familial, and academic responsibilities. Exacerbating the mental health crisis is the fact that students are facing other societal crises (e.g., climate change). And, in a reciprocal fashion, students experiencing poor mental health are less likely to feel resilient enough to tackle these other crises. In response to these colliding societal crises, we need a comprehensive solution that goes beyond the current models of college mental health services. We propose an alternative preventative mental health approach, which aims to prevent the onset of mental health concerns and build resilience in the face of colliding crises. Specifically, we argue that colleges can aid in building mental health resilience by creating for-credit courses that teach students the skills they need to be conscious, responsible, and resilient human beings. Toward this end, we created an experiential, workshop-style, 1 unit, P/NP course, entitled “Learning Sustainable well-being” (LSW), which guides students to explore, improve, and sustain their mental health. The principles taught in this course combine the wisdoms of several disciplines, including mindfulness, psychology, neuroscience, philosophy, religion, poetry, and cinema. The following community case study reflects on the journey of our “LSW initiative,” starting from the creation of the course in 2014 to the current mission of scaling up the offering as part of an institution-wide LSW program. To this end, we describe the LSW course modules/content, our pedagogical approach, potential limitations, and then provide data demonstrating its efficacy in improving student well-being. As a final note, we present the challenges we have faced, and the lessons learned, while on this journey. We hope that presenting this community case study will facilitate the growing dialogue across colleges about creating (and perhaps requiring) courses like LSW in order to improve students’ mental health and resilience in the context of other colliding crises.